2017
DOI: 10.1021/acs.biochem.7b00556
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Promotes the Recovery of Mycobacterium tuberculosis β-Lactamase from Clavulanic Acid Inhibition

Abstract: The rise of multi- and even totally antibiotic resistant forms of Mycobacterium tuberculosis underlines the need for new antibiotics. The pathogen is resistant to β-lactam compounds due to its native serine β-lactamase, BlaC. This resistance can be circumvented by administration of a β-lactamase inhibitor. We studied the interaction between BlaC and the inhibitor clavulanic acid. Our data show hydrolysis of clavulanic acid and recovery of BlaC activity upon prolonged incubation. The rate of clavulanic acid hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 44 publications
(102 reference statements)
6
54
0
Order By: Relevance
“…The chemical shift difference between the major and minor state must be larger than 0.1 ppm for 1 H and/or 1 ppm for 15 N at 20 T. The link between these four residues is that in every BlaC crystal structure published to date, their respective sidechains each contribute to the hydrogen bonding with either the carboxyl group of a ligand or a phosphate or acetate ion from the buffer. However, upon titration with phosphate, the resonances do not appear, (31) that, if binding occurs at all, the affinity must be very low indeed and line broadening in the BlaC NMR spectrum was not observed. (49) Therefore, we attribute the increased dynamics to the adduct formation.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical shift difference between the major and minor state must be larger than 0.1 ppm for 1 H and/or 1 ppm for 15 N at 20 T. The link between these four residues is that in every BlaC crystal structure published to date, their respective sidechains each contribute to the hydrogen bonding with either the carboxyl group of a ligand or a phosphate or acetate ion from the buffer. However, upon titration with phosphate, the resonances do not appear, (31) that, if binding occurs at all, the affinity must be very low indeed and line broadening in the BlaC NMR spectrum was not observed. (49) Therefore, we attribute the increased dynamics to the adduct formation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…We recently characterized the timescale of interaction between the β-lactamase of Mycobacterium tuberculosis, BlaC (Figure 1), and the inhibitor clavulanic acid in different buffers. (31) The high stability of the complex in MES buffer opens up a window for NMR dynamics measurements. Also the effects of the inhibitor avibactam, which binds reversibly rather than being degraded,(32) can be measured using these techniques.…”
mentioning
confidence: 99%
“…β-Lactam/β-lactamase combination therapies were shown to be effective in killing Mtb in vivo and in vitro . 813 BlaC inhibition by clavulanic acid was initially thought to be permanent, but later it was observed that BlaC enzymatic activity recovers very slowly from inhibition, with 50% reached after 14 h. 14 Recovery from inhibition by sulbactam and tazobactam was reported to occur after 30 and 45 min, respectively, 2 while recovery from avibactam inhibition took 48 h. 15 Furthermore, it was shown that the rate of recovery of BlaC activity after clavulanate inhibition is strongly dependent on the ions that are present in the buffer, such as phosphate, acetate, or sulfate, with phosphate and sulfate triggering BlaC recovery, and acetate slowing it down. 14 A possible pathway of BlaC inhibition by clavulanate was suggested by Hugonnet and colleagues 2 based on mass spectrometry (MS) and crystallographic data (Figure 2).…”
mentioning
confidence: 99%
“…813 BlaC inhibition by clavulanic acid was initially thought to be permanent, but later it was observed that BlaC enzymatic activity recovers very slowly from inhibition, with 50% reached after 14 h. 14 Recovery from inhibition by sulbactam and tazobactam was reported to occur after 30 and 45 min, respectively, 2 while recovery from avibactam inhibition took 48 h. 15 Furthermore, it was shown that the rate of recovery of BlaC activity after clavulanate inhibition is strongly dependent on the ions that are present in the buffer, such as phosphate, acetate, or sulfate, with phosphate and sulfate triggering BlaC recovery, and acetate slowing it down. 14 A possible pathway of BlaC inhibition by clavulanate was suggested by Hugonnet and colleagues 2 based on mass spectrometry (MS) and crystallographic data (Figure 2). The MS data suggested the formation of four main covalent intermediates corresponding to MS peaks +70, +137, +155, and +199 Da compared to a free enzyme, 2,14,16 while BlaC crystal soaking with clavulanic acid and the X-ray crystal structure determination allowed for trapping a covalent adduct corresponding to the +155 Da MS peak (PDB 3CG5, Figure 2d).…”
mentioning
confidence: 99%
See 1 more Smart Citation